Karakterisasi Dan Uji Daya Hasil Bawang Merah (Allium accalonicum L.) Lokal Asal Maluku Barat Daya - Hetharie, Piero; Laisina, Jane K J; Hehanussa, Meity L (Universitas Pattimura, 2024)
The development of local shallots originating from Southwest Maluku (MBD) needs to be improved through registration and release of varieties, characterization, and yield testing activities, which are one of the stages of activities to support variety registration and release. Therefore, this research aims to describe the morphological characteristics and test the yield of several local varieties of shallots originating from MBD. This research was conducted on Lakor Island, Southwest Maluku Regency, from October 2022 until completion. The study was conducted using a Randomized Complete Block Design consisting of 4 accessions of Lakor Island shallots conducted in 3 replications, resulting in 12 experimental units, with a planting distance of 15 × 15 cm. There is morphological diversity in local shallots originating from the Southwest Maluku Regency, and the cluster results based on 16 qualitative characteristics showed that the Lolotuwara variety is 99% similar to the Letoda variety. Lolotuwara and Letoda have a 94% similarity to the Letpey variety, while the Lolotuwara, Letoda, and Letpei varieties have a 75% similarity. The analysis of variance results showed significant diversity for bulb weight characteristics. In contrast, the number of bulbs per clump did not differ significantly, whereas the Lolotuwara variety had the highest bulb weight compared to other local varieties.